Influence of attitude on online impulse buying: perspective on marketing communication - Dharta, Firdaus Yuni; Prasetyo, Hemi; Dema, Yosef (Jurnal Studi Komunikasi, 2021)
The purpose of this study is to investigate the impact of government policy, marketing communication, and website quality on online impulse purchases. The effect of attitude mediation on government policy relations, marketing communications, and the quality of website and online impulse buying is also analysed in this research. This research is survey research with a sample of respondents as many as 250 active students in West Java. Data analysis in this research is path analysis using PLS-SEM. The findings of this study show that government legislation, marketing messaging, and website quality all have a direct impact on online impulse purchase. The attitude examined in this study is unable to counteract the impact of government legislation and commercial communications on online impulse purchases. However, attitude can mitigate the impact of website quality on online impulse purchases.